Positif Correlation of Anxiety and the Interest of Elderly in Visiting Health Facilities During the COVID-19 Pandemic - Pria Wahyu Romadhon Girianto; Dwi Setyorini; Sri Untaminingtyas (STIKes Patria Husada Blitar, 2023)
Anxiety about dealing with the infectious nature of COVID-19 could influence the elderly to avoid visiting health facilities due to concerns about the rapid transmission of the disease. The impact of decreasing interest in visiting the elderly with comorbidities to health facilities causes repeated recurrences, and they do not get treatment to improve their health. This research aimed to determine the correlation between anxiety and interest in visiting health facilities for the elderly with comorbid diseases during the COVID-19 pandemic. The variables in this research were anxiety and interest in visiting health facilities. A questionnaire was used for data collection. The design of this research was a correlation with a cross-sectional approach, a sample of 32 respondents, and a purposive sampling technique. The result showed that most of the respondents (53.1%), 17 respondents, experienced moderate anxiety. Most of the respondents (62.5%), 20 respondents, had sufficient interest in visiting. Based on the Spearman's rank test, a p-value of 0.032 (Î± = 0,05) was obtained, meaning that there was a correlation between anxiety in comorbid elderly people and interest in visiting health facilities during the COVID-19 pandemic with a weak correlation category (r = 0.380). The elderly's anxiety about visiting health facilities during the pandemic could be because the elderly are getting tired of the comorbid disease process they experience; the elderly also feel vulnerable to infection due to information related to COVID-19 transmission; the elderly were afraid to die when confirmed with COVID-19; the elderly worried about the health of their families and the elderly as well. Worried that they have contracted the COVID-19 virus. It recommended for respondents not be afraid or anxious about coming to health facilities during the COVID-19 pandemic. The elderly could visit health facilities during the COVID-19 pandemic safely by always complying with health protocols